Barriers to private electricity provider in Cambodia : analyzing the social, institutional and economic pressures of rural electricity enterprises - Soveasna Sun; Do, Ba Khang; Broustai, Joel Francois; Zimmerman, Willi; Government of French; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2004)
Because of the low electrification rate, the electricity price in Cambodia is the highest in the region and some of the highest in the world. Particularly, in rural areas electricity pricing is range of USD 0.30 - 0.90 per kWh. Electrification rate is only 20% of the total country's households and 12% of the total rnral households. The average use of electricity in Cambodia is 55 kWh per year per person The supply shortage is the combined result of inefficiencies created by old generating equipment, reliance on fully impo1ted diesel fuel and large losses in low quality medium voltage distribution systems, uncompetitive market structures, and the lack of a legal framework, investment framework, and administrative capabilities. The study describe the challenges which private electricity suppliers in Cambodia faces with including commercial, technical and institutional problems. The study focuses mainly on institutional problem which reflects the shortage of Government policy implementation on private sector pa1ticipation.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M. BA.) - Asian Institute of Technology, 2004
Keywords: Rural electrification -- Cambodia; Electric industries -- Cambodia; Electricity